Enhancing basketball technique learning using I-spring application: A study in high school physical education - Saputro, Hadi; Kurniawan, Rama; Saputra, Surya Adi; Wahyudi, Usman (CV Rezki Media, 2025)
Background: High school students feel less able to master the subject of Physical Education, Sports, and Health (PJOK) Basketball material in a relatively short meeting, so it needs innovative learning. Objectives: This research was conducted to develop learning media for basketball game material based on the I-Spring application to facilitate students' learning. Methods: This research uses the Research and Development (R&D) method using the ADDIE model, which refers to Lee and Owens. Data collection was done through direct observation and questionnaire distribution. The research subjects were the students of Senior High School 1 Gondanglegi, Malang Regency, Indonesia, which amounted to 866 students. The data analysis method used is descriptive qualitative using Likert scale calculation. Results: The observation results showed that 95.5% of students had participated in basketball learning in class or on the field, 71.2% of students had difficulty learning the basic techniques of basketball games, and 92.4 students needed application-based learning media to understand more deeply and be able to practice basic basketball techniques. Small group trials on 10 students obtained results of 85.2% and 86.4% for large group trials with 30 students. Conclusions: The developed product is feasible for PJOK learning, especially basketball material at State Senior High School 1 Gondanglegi. Future studies are encouraged to expand the material coverage and evaluate long-term learning outcomes using the developed application.